1995
DOI: 10.1007/bf00188188
|View full text |Cite
|
Sign up to set email alerts
|

On the degradation of conducting Langmuir-Blodgett films

Abstract: Direct current through conducting Langmuir-Blodgett films was observed as a function of the applied voltage and alternating current as a function of frequency. In some cases voltage-current characteristics appeared to be quasi-ohmic but in other cases they exhibited tunnelling-like behaviour. This phenomenon was interpreted as being due to the progressive detachment of the film from the micro-electrodes, as confirmed by measurements of the conductivity as a function of time. This interpretation was also confir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…It was also shown that the differentiation in fragment distributions with testing rate is evident at strain values much lower (Ϸ2.5%) than the strain typically required to complete the test (Ϸ4.2%). These results are consistent with the existence of stress concentrations at the end of broken fragments as described by Carrara and McGarry [10] and Jahankhani and Galiotis [11]. These stress concentrations can initiate failure of the fiber-matrix interface on the molecular level.…”
Section: Introductionsupporting
confidence: 90%
“…It was also shown that the differentiation in fragment distributions with testing rate is evident at strain values much lower (Ϸ2.5%) than the strain typically required to complete the test (Ϸ4.2%). These results are consistent with the existence of stress concentrations at the end of broken fragments as described by Carrara and McGarry [10] and Jahankhani and Galiotis [11]. These stress concentrations can initiate failure of the fiber-matrix interface on the molecular level.…”
Section: Introductionsupporting
confidence: 90%
“…It can be explained by taking into account that the thickness of a single monolayer is nearly 24 ± 1 Å, while the height of the electrode is 40 nm. So, it is possible to have some breaking of the film at the electrode . When the potential is reversed, the hysteresis in the current−voltage can be observed.…”
Section: Resultsmentioning
confidence: 99%
“…Strong intermolecular interactions give rise to stable oligothiophene layers, which are essential for device fabrication. Under extreme electrical or thermal conditions, conductive oligothiophene film can degrade via progressive detachment of the adsorbates . While the threshold of thermal and electrical stability has been studied, the stability while exposed to various solvents has yet to be systematically investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Under extreme electrical or thermal conditions, conductive oligothiophene film can degrade via progressive detachment of the adsorbates. 25 While the threshold of thermal and electrical stability has been studied, the stability while exposed to various solvents has yet to be systematically investigated. This work investigates the structure of oligothiophene LB films upon exposure to aqueous media, to evaluate the stability and determine if molecular level packing is interrupted.…”
Section: ■ Introductionmentioning
confidence: 99%